Accuracy of Intraoperative Frozen Section in Diagnosing Malignancy of Ovarian Neoplasm - Utami, Tofan W; Iskandar, Jasmine; Tanamas, Gregorius; Jamtani, Mona; Nuranna, Laila; Nuryanto, Kartiwa H (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To evaluate the accuracy of frozen section for ovarian neoplasm in our hospital. Method: A retrospective evaluation was conducted on medical records of patients with ovarian neoplasms who underwent a frozen section laparotomy between the years 2008 and 2013 at Dr. Cipto Mangunkusumo Hospital. Records with incomplete data on frozen section or paraffin block report were excluded. Criteria for frozen section laparotomy in our facility was based on a malignancy score of equal to or more than 6. Frozen section reports were compared to paraffin block report based on benign, borderline, or malignant cases. Result: From 139 patients with ovarian neoplasm, only 91 patients fulfilled the inclusion and exclusion criteria. Frozen section examination revealed benign cases was 15.4%, borderline cases was 15.4%, and malignant cases was 69.2%. Based on histopathological type, clear cell cystoadenocarcinoma was the most commonly observed histotype (19.8%). The sensitivity of frozen section for benign, borderline, and malignancy cases respectively was 81.8%, 76.9%, 91.0%. The specificity of frozen section for benign, borderline, and malignancy case respectively was 93.8%, 94.8%, 91.6%. Conclusion: We found that the accuracy of intraoperative frozen section in our facility is adequate to diagnose ovarian neoplasm and can be used to assist in determining the extent of surgical management. [Indones J Obstet Gynecol 2015; 3: 161-164] Keywords: frozen section, ovarian neoplasm, paraffin block, sensitivity, specitificity